Worldwide Variations in Fluoride Content in Beverages for Infants - Eleonor Velez-León; Edisson-Mauricio P; Mario Díaz-Dosque; Daniela Tobar-Almache (MDPI AG, 2023)
In situations where breastfeeding is impractical, milk formulas have emerged as the primary choice for infant nutrition. Numerous global studies have scrutinized the fluoride content in these formulas, uncovering fluctuations in fluoride levels directly associated with the method of preparation. This variability poses a potential risk of elevated fluoride concentrations and, consequently, an increased susceptibility to dental fluorosis in infants. The primary objective of this review is to intricately delineate the fluoride content in dairy formulas and emphasize the variability of these values concerning their reconstitution process. The review's findings reveal that, among the 17 studies assessing fluoride levels in infant formula, milk-based formulas exhibit a range of 0.01-0.92 ppm, with only two studies exceeding 1.30 ppm. Conversely, soy-based formulas demonstrate values ranging from 0.13-1.11 ppm. In conclusion, the observed variability in fluoride levels in infant formulas is ascribed to the choice of the water source employed in the preparation process. This underscores the paramount importance of meticulously adhering to recommendations and guidelines provided by healthcare professionals concerning the utilization of these formulas and their meticulous reconstitution.